Corn Oil Supplementation Enhances Locomotor Performance and Mitochondrial Function in Drosophila melanogaster - Jadyellen Rondon Silva; Thiago Henrique Oliveira Alves; Eric Bruno Silva Santos; Marylu Mardegan Lima; Giulia Covolo Spegiorim; Carlos Antônio Couto-Lima; Luciane Carla Alberici; Marcos José Jacinto; Anderson Oliveira Souza (Applied Sciences, 2025)
Polyunsaturated fatty acids are vital for brain health, supporting cognitive development and helping to prevent neurodegenerative diseases. Since the body cannot produce them, they must be obtained through food. This study aimed to assess the effects of corn oil on the behavior and biochemical parameters of Drosophila melanogaster. The flies were fed a diet supplemented with different concentrations of corn oil from the larval stage until the fifth day of adulthood. A diet containing corn oil (37.8 mg/mL of linoleic acid) reduced mortality under starvation conditions and enhanced locomotor performance (p < 0.01). Biochemical analyses revealed increased levels of glutathione (p < 0.001), citrate synthase activity (p < 0.05), and mitochondrial phosphorylation (p < 0.05), indicating a potential boost in energy metabolism. Conversely, a decrease in acetylcholinesterase activity (p < 0.05) was observed, suggesting cholinergic modulation. These results demonstrate that corn oil supplementation supports neural health in this animal model, opening pathways for further research into non-pharmacological treatments for neurodegenerative diseases such as Alzheimer’s disease.